In this article we will learn about Transformation

Transformation |

**SinC+SinD= 2Sin(C+D/2)Cos(C-D/2)****SinC-SinD= 2Cos(C+D/2)Sin(C-D/2)****CosC+CosD= 2Cos(C+D/2)Cos(C-D/2)****CosC-CosD= 2Sin(C-D/2)Sin(D-C/2)****2SinACosB=Sin(A+B)+Sin(A-B)****2CosASinB=Sin(A+B)-Sin(A-B)****2CosACosB=Cos(A+B)+Cos(A-B)****2SinASinB=Cos(A-B)-Cos(A+B)**

I hope you have find this article helpful. If you like this article then you can share this article with your friends also you can Subscribe to our blog. I will try to update all useful Mathematical Formula. Thanks for reading this article.

## Comments

## Post a Comment